An Evaluation of Environmental Performance According to The International Standard (ISO14001: 2015) in a Field East of Baghdad / A Case Study in the Midline Oil Company - Jasim Resen, Ekhlas; Sadiq AbdulRazzaq, Mohammed (Journal of Economics and Administrative Sciences, 2022)
EMS in accordance with ISO 14001: 2015 is considered an entry point to reduce environmental impacts, especially the effects resulting from the oil industry, which is the main source of environmental pollution and waste of natural resources, since the second revision of the standard took place in September 2015. The problem of the research was manifested in the weakness in understanding the correct guidelines that must be followed in order to obtain and maintain the standard. The purpose of this research was to give a general picture of what is behind ISO14001:2015 and how it is possible to create a comprehensive base for understanding its application by seeking the gap between the actually achieved reality, standards requirements, and the diagnosis of their causes in the Medline Oil Company/ A field east of Baghdad by using the checklist and a number of statistical analysis methods (arithmetic mean, weights and percentages). The research reached a number of results; the most important of which is the existence of a gap in the application of the standard at a rate of (47.03%) resulting from a weakness in the application of most of the standard’s clauses in the company and lack of interest in the programs related to the treatment and reduction of environmental impacts. The added value in this research is evident by diagnosing the strengths and weaknesses in each clause of the environmental specification in preparation for setting plans to eliminate or reduce the gap in the company under consideration.  Paper type: Case research.